Advanced Materials for Printed Wearable Electrochemical Devices: A Review. (7th December 2016) - Kim, Jayoung; Kumar, Rajan; Bandodkar, Amay J.; Wang, Joseph
Abstract : The field of printed wearable electronics has witnessed spectacular growth due to its promise to offer low‐cost, high‐performance devices for a broad range of applications. Among the sub‐fields of printed wearable electronics, printed wearable electrochemical systems are of special importance due to their widespread applications in healthcare, energy and security fields. These systems have opened up new avenues for body‐integrated electronics that were earlier impossible to achieve. These include wearable energy systems and sensors for a wide variety of applications. Much of the success of printed wearable electrochemical systems can be attributed to innovations in materials engineering that have led to novel inks comprising of new nanomaterials, polymers and composites. New generation of printed electrochemical devices include soft, stretchable and anatomically‐compliant devices that enable efficient bio‐integration and withstand high tensile stress associated with on‐body applications. Progress in materials science has also led to the development of self‐healing printed electrochemical systems for wearable applications. This review provides an overview of the key material requirements for ink formulations for realizing efficient wearable electrochemical systems such as batteries, supercapacitors, biofuel cells and sensors. Finally, major challenges impeding the field of wearable electrochemical systems are discussed along with future prospects of this exciting field. Abstract : Recent advances in the development of new ink materials that meet the demands of wearable electrochemical devices are discussed. Particular attention is given to innovations in materials engineering that have led to novel inks comprising of new nanomaterials, polymers and composites. Such developments offer considerable promise for realizing efficient wearable electrochemical systems such as batteries, supercapacitors, biofuel cells and sensors.